Fluidic Capacitive Sensor for Detection of Air Bubble Inside Engine Lubricating Oil - Hải, Nguyễn Đắc; Tuấn, Vũ Quốc; Hà, Trần Thị Thúy; Minh, Nguyễn Ngọc; Trình, Chử Đức (VNU Journal of Science: Natural Sciences and Technology, 2015)
In this paper, a capacitive sensor based on printed circuit board was designed and fabricated to detect air bubbles that appear in the engine lubricating oil. A three-electrode capacitive sensor structure is designed and simulated for monitoring and estimating amount and size of air bubbles in oil. The capacitive sensor consists of three electrodes that are structured by the PCB, copper sheets and vias. The oil pipe as a fluidic channel is threaded through the hole of capacitive sensor. By using that structure, air bubble inside fluidic channel can be detected in real-time monitoring.  Simulations showing the change of signal in correspondence to the volume of air bubble inside oil channels are compared to the measurement to give a good idea of fabrication structure. In this measurement, this capacitive sensor can monitor an air bubble with a small size of 0.1 mm 3 to 3.83 mm 3 . The occurring of multi air bubbles is also monitored by this capacitive sensor for distinguishing each bubble when the bubbles have a small distance among them. Keywords : Capacitive sensor, Fluidic sensor, Air bubble detection.